Development of Banana Stem Drink from Musa × paradisiaca L. - Zaini, Nur Farah Hazwani (Enhanced Knowledge in Sciences and Technology, 2022)
Development of banana stem drink is an effort to overcome the problem of beverage with energy dense and nutrient poor in the market, the banana stem drink will be one way to ensure customers can enjoy a refreshing drink besides can receive a variety of nutrients from the banana stem. The study aims to produce a low-calorie banana stem drink and to evaluate the sensory properties of the banana stem drink. Besides, this study also aims to analyze the antioxidant activity, physicochemical properties and nutritional composition of the banana stem drink. To produce the drink, banana stems which are Berangan banana stem, Jackfruit banana stem and Rhino Horn banana stem were undergo a sample preparation process to produce a banana stem extract. Next, the drink will be formulated by adding several ingredients to produce a desirable drink. After the development process of the drink is complete, the banana stem drink will undergo a sensory evaluation test, antioxidant properties and physicochemical analysis which are pH, sugar brix, colour and titratable acidity. Based on the sensory evaluation, all of the formulations showed the significantly different (p < 0.05) in term of overall acceptance. Formulation 2 highest degree of overall acceptance with 6.7 ± 1.76. Meanwhile, the least favourable sample by panelists is control sample with 5.8 ± 1.91. For the antioxidant activity, the highest percentage of scavenging activity is Formulation 4. The formulation consists of all three types of banana stem extract and that is why it has higher antioxidant activity. Based on the results obtained, banana stem drink is a beverage with low pH and low sugar content. It also has brighter colour, less red and more yellow than control sample.